Nurses’ Ethical Reasoning About Digital Ethical Risks: A Vignette‐Elicited Qualitative Study - Betül Bal; Nagihan Köroğlu Kaba; Emine Apaydin (International Nursing Review, 2026)
ABSTRACT Aim This qualitative study aimed to explore how nurses reason ethically about potential digital ethical risks arising from the routine use of digital systems in clinical practice and the strategies they propose to address these risks in response to vignette‐based scenarios. Background Digital systems shape nursing documentation, monitoring, communication, education, and decision‐making. Although they support care, digital ethical risks may arise when digital outputs are accepted without clinical verification, patients are not adequately informed, or data protection is weak. Design A vignette‐elicited qualitative design was used. Methods The study was conducted in September 2025 with 16 nurses working in three public hospitals in Central Anatolia, Türkiye. Data were generated through face‐to‐face interviews using seven vignette‐based scenarios and analyzed using Braun and Clarke's reflexive thematic analysis. Results Three main themes were generated through the analysis of nurses’ ethical reasoning in response to the vignette‐based scenarios: (i) nurses’ purposes for using digital systems, (ii) digital ethical risks in nursing, and (iii) strategies to prevent digital ethical risks. The findings within Themes 2 and 3 were organized into four subthemes—nonmaleficence and beneficence, autonomy and respect for persons, justice and equity, privacy and confidentiality—and further structured across three researcher‐developed categories: nurse, digital system, and organization. Conclusions Participants’ interpretations of the vignette‐based scenarios highlighted potential digital ethical risks that may require nurses to combine clinical judgment with ethical reasoning when using digital systems. Implications for Nursing Participants’ responses may inform digital ethics education by highlighting the importance of verifying digital data through bedside assessment, questioning potentially unsafe digital outputs, protecting confidentiality, obtaining meaningful consent, and recognizing potential risks in documentation, alarms, communication, and data sharing. Implications for Health Policy Participant‐identified priorities may inform institutional consideration of protocols for documentation, alarm management, mobile communication, image sharing, access control, patient information, accessibility, and accountability in digital nursing care.